The elements of management parameters of radar tracking for aircraft - V. V. Lavina; L. E. Rudelson (Научный вестник МГТУ ГА)
The increase of flow capacity of air space demands high precision of surveillance and the organization of such actions, as reducing selection norms, flights on free trajectories, transfer of part of controller's functions to the pilot. It is as-sumed that technical support of such innovations will be carried out on the basis of automatic dependent surveillance-broadcast. The complete elimination of radar maintenance, despite a high error of measurements, isn't rational because failure of the onboard equipment conducts to loss on the earth of current measurement information. In the article the pos-sibilities of improvement of quality of processing of radar information as the surveillance instrument which doesn't depend on a technical condition of the onboard equipment are discussed.